(untitled) (Historia, 2021)
The City Council of Bloemfontein failed to provide in the housing needs of Mangaung, which resulted in serious overcrowded and unhealthy living conditions. It would be unfair however, to blame without more ado the City Council as solely responsible for this state of affairs. There were indeed a medley of economic, political and administrative circumstances present in the departmental structures of both the Bloemfontein Municipal Government and Central Government which were responsible for the alarming extent of the housing shortage. Their favouring of White socio-economic interests for the sake of political gain in the context of racial segregation was fatal to Mangaung’s housing shortage